PENGARUH TERAPI CAM SELEDRI TERHADAP TEKANAN DARAH PADA LANSIA DI UPTD PUSKESMAS KUALA SEMPANG - Rayanti, Rayanti; Abdullah, Endang; Rahman, Zakiah (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Hypertension generally occurs without symptoms (asymptomatic). Most people do not feel it, even though their blood pressure is far above normal. Treatment for hypertension can be done non-pharmacologically, traditional medicine (herbal) treatment. One of the non-pharmacological treatments is celery cam therapy. The purpose of this study was to determine the effect of celery cam therapy on blood pressure in the elderly at UlPTD Pulskelsmas Kulala Selmpang. The research method is a qualitative research with a pretest-posttest with control group design. The questionnaire was conducted. The sample was 36 respondents. The sampling technique was purposive sampling. Univariate data analysis of the majority in the elderly age range (elderly) 60-74 years as many as 33 respondents (91.7%), gender is mostly female 30 respondents (83.3%) education is mostly elementary school 22 respondents (61.1%), and the duration of hypertension <5 years is mostly majority 30 respondents (83.3%). Bivariate analysis using the Wilcoxon test with a p value of 0.000 there is an influence of celery therapy on blood pressure in the elderly at UlPTD Pulskelsmas Kulala Selmpang. The conclusion of celery therapy shows a positive effect in lowering blood pressure in the elderly because celery contains compounds such as phthalides, which can help relax the walls of the arteries and increase blood flow and contain flavonoids, saponins, tannins, essential oils and apigelnin which are efficacious as tonics that stimulate digestive enzymes, Regular consumption of celery can help control hypertension. Celery therapy